Transtorno do Espectro Autista na adolescência: revisão integrativa sobre as contribuições da neurociência para o processo educacional destes(as) educandos(as) - Simanovicius, Marcia Aparecida De Lima [UNIFESP] (2020)
Brazil has, over the past few years, been a signatory to various agreements and declarations, to which it has committed itself to organizing, implementing and implementing public policies, to guarantee the rights of access, permanence, participation and learning of the students, target audience of Special Education (with disabilities, global developmental disorder / autism spectrum disorder and high skills / giftedness) in regular schools, whether public, private, denominational or philanthropic. In this context, we have identified that one of the greatest challenges is the educational process of people with Autism Spectrum Disorder. We understand that neuroscience and recent scientific evidence on brain functioning, bring light to the learning processes, and may point out ways to qualify the teaching work in serving these students.